2018
DOI: 10.1088/2053-1591/aae8f3
|View full text |Cite
|
Sign up to set email alerts
|

Finite element and experimental investigation on the effects of temperature, strain and strain rate on microstructure and mechanical properties of FSSWed TRIP steel joints

Abstract: Finite element and experimental investigation on the effects of temperature, strain and strain rate on microstructure and mechanical properties of FSSWed TRIP steel joints To cite this article before publication: Ali Ebrahimpour et al 2018 Mater. Res.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Utilizing analysis of variance, the direct, quadratic, and interactive impacts of the parameters on the responses were scrutinized, culminating in the formulation of a distinct mathematical model for each response. In particular, current density had the most significant impact on all responses [8].…”
Section: Introductionmentioning
confidence: 98%
“…Utilizing analysis of variance, the direct, quadratic, and interactive impacts of the parameters on the responses were scrutinized, culminating in the formulation of a distinct mathematical model for each response. In particular, current density had the most significant impact on all responses [8].…”
Section: Introductionmentioning
confidence: 98%
“…Results indicated that the arrangement of one row of four joints perpendicular to the loading direction is the best as it has highest fatigue strength. Ebrahimpour et al [ 11 ] investigated the TRIP steel sheets jointed by the FSSW process for different rotational speeds experimentally and numerically. FEM was employed to calculate the effects of temperature, strain, and strain rate during the welding process.…”
Section: Introductionmentioning
confidence: 99%